2015
DOI: 10.1097/jcn.0000000000000191
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Physical Symptom Biology in Heart Failure

Abstract: Background There are several gender differences that may help explain the link between biology and symptoms in heart failure (HF). Objective The aim of this study was to examine gender-specific relationships between objective measures of HF severity and physical symptoms. Methods Detailed clinical data, including left ventricular ejection fraction and left ventricular internal end-diastolic diameter, and HF-specific physical symptoms were collected as part of a prospective cohort study. Gender interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…One explanation for more women being in the HSS group may be related to physiological differences in the ventricular size and function in women and men with HF. 28 For instance, it has been shown that women with HF have smaller and stiffer ventricles with higher filling pressures than men, possibly contributing to more physical symptoms in women with HF. 28,29 In addition, our observation that women were significantly more likely to be in the HSS group may explain, in part, reports from other studies describing women with HF having lower health-related quality of life compared to men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One explanation for more women being in the HSS group may be related to physiological differences in the ventricular size and function in women and men with HF. 28 For instance, it has been shown that women with HF have smaller and stiffer ventricles with higher filling pressures than men, possibly contributing to more physical symptoms in women with HF. 28,29 In addition, our observation that women were significantly more likely to be in the HSS group may explain, in part, reports from other studies describing women with HF having lower health-related quality of life compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…28 For instance, it has been shown that women with HF have smaller and stiffer ventricles with higher filling pressures than men, possibly contributing to more physical symptoms in women with HF. 28,29 In addition, our observation that women were significantly more likely to be in the HSS group may explain, in part, reports from other studies describing women with HF having lower health-related quality of life compared to men. 30,31 Thus, our study highlights the importance of gender in HF, and suggests clinicians and researchers consider gender in developing treatment plans and research projects addressing HF symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is more recent evidence of biomechanical underpinnings of HF symptoms 13,14 as well as biochemical links between symptoms and HF severity including an objective metric of adrenergic dysregulation that was shown recently to be associated with a composite score of physical HF symptoms. 15 Hence, one reason for limited evidence connecting symptoms and objective markers of HF may be that we have been looking at the wrong metrics to test such associations.…”
Section: Introductionmentioning
confidence: 99%
“…hemodynamics) and what patients experience symptomatically, [4][5][6] this is an important next step in identifying a biological underpinning of physical symptoms in HF. These findings, coupled with other advances in HF symptom biology, 19,20 could inform conversations in clinical settings, especially when eliciting information regarding symptom burden. Moreover, these results could provide an amenable target for ameliorating symptom burden through interventions directed at reducing sympathetic overdrive, including a combination of pharmacological, exercise, and self-care interventions.…”
Section: Discussionmentioning
confidence: 89%